y = - 3
Since y varies directly as x then
y = kx ← ( k is the constant of variation )
to find k use y = - 1 when x = 3
k =
=
= - ![\frac{1}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D)
hence y = -
x
when x = 9, then
y = -
× 9 = - 3
Answer:
y = -5x - 23
Step-by-step explanation:
Point-slope form:
y - 7 = -5(x + 6)
rearrange:
y - 7 = -5x - 30
y = -5x - 23
Answer:
The function f(x) = -9.5 + 6 + x² is neither odd or even.
Step-by-step explanation:
We know that a function is termed as 'even' when
f(-x) = f(x) for all x
We know that a function is termed as 'odd' when
f(-x) = -f(x) for all x
Given the function
f(x) = -9.5x⁵ + 6 + x²
substitute x with -x
f(-x) = -9.5(-x)⁵ + 6 + (-x)²
as (-x)⁵ = -x⁵, so
f(-x) = -(-9.5x)⁵ + 6 + (-x)²
Apply exponent rule: (-a)ⁿ = aⁿ, if n is even
f(-x) = -(-9.5x)⁵ + 6 + x²
Apply rule: -(-a) = a
f(-x) = 9x⁵ + 6 + x²
As
f(-x) ≠ f(x) ≠ -f(x)
Therefore, the function f(x) = -9.5 + 6 + x² is neither odd or even.